Women Who Lead: Successes and Challenges of Five Health Leaders. Issue 3 (2nd July 2016) - Javadi, Dena; Vega, Jeanette; Etienne, Carissa; Wandira, Speciosa; Doyle, Yvonne; Nishtar, Sania
Abstract: Women make up approximately 75% of the health workforce and yet their representation at higher levels of health leadership is limited. Untapped potential of women in health undermines the contribution they could make to effective leadership for health systems strengthening. Lived experiences of women leaders can help understand how to unlock this potential by identifying the challenges, highlighting enablers, and sharing successful strategies used to become effective health leaders. This article uses phenomenological inquiry to understand the subjective experiences of five influential women in their paths to health leadership. Interviews were conducted with these women and key messages were identified. A grounding theme—defined as the essential element for the subjective experience of leading as a woman in the health system—was revealed to be the women's "drive for equity." This drive motivated them to pursue a career in health and to break through perceived gender-related barriers. Three figural themes around how to practice effective health leadership to promote equity were identified: (1) challenging status quos and norms; (2) leading by listening and leveraging others' expertise to build a common vision for health; and (3) having social support early on to develop confidence and credibility. Stories from the individual women's experiences are presented. Finally, three recommendations are made for system-level mechanisms that could contribute to expanding the number of women leaders in health.